Transformation Of Islamic Education Learning Management: Integration Of Computer-Based Tests And Ethical Values Of Evaluation In Islamic Education - Rafika Nisa (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
The digital transformation of educational assessment has accelerated the adoption of Computer-Based Tests (CBT) in Islamic Religious Education (PAI). Although CBT improves efficiency and objectivity, it also raises concerns regarding students’ academic anxiety and the integration of Islamic ethical values in evaluation practices. This study aims to explore students’ experiences of academic anxiety during CBT implementation in PAI, identify technical, pedagogical, and ethical factors influencing anxiety, and examine how Islamic evaluation ethics are applied in computer-based assessments. Using a qualitative interpretive approach with a case study design, data were collected through in-depth interviews, observations, and document analysis involving PAI teachers, students, school leaders, and CBT operators in an Islamic educational institution. The findings indicate that CBT generates significant academic anxiety manifested in cognitive, emotional, and physiological responses, primarily due to technical uncertainty, rigid assessment design, and perceptions of limited tolerance for errors. Evaluation management remains largely technocratic, emphasizing system efficiency over students’ psychological well-being. Although educators demonstrate normative understanding of Islamic ethical principles—such as justice (al-‘adl), trustworthiness (amanah), compassion (rahmah), and public benefit (maslahah)—these values are not yet systematically integrated into CBT policies. Nevertheless, practices such as CBT simulations, spiritual reinforcement, transparent procedures, and technical support were found to reduce anxiety. The study concludes that integrating Islamic ethical values into CBT-based evaluation management is essential to creating fair, humane, and educational digital assessment in Islamic education